Hip-hop Crossroads of the Popular, Political and Funny in Media Music from Bulgaria (Seminar_BG, 2023)
The study offers observations on some trajectories of the funny in Bulgarian hip-hop situated at the crossroads of popular culture and popular politics. The subject of the analysis is hip-hop videos of artists (“Upsurt”, Itzo Hazarta, Jluch) that have huge popularity on the web due to the political messages in their songs to a large extent. Through analytical readings of lyrics, performance, visual narratives in the videos, and media narratives of the artists and tracks, the study shows how in the free internet environment these hip-hop performative messages exist as the protester’s choices, alternative journalism, weapons on the communication front to vilify the adversary, subversive resources through the comic and parody.  ReferencesAvramov, Asen. 2021. „Dumi v deystvie (Opit za vgrazhdane na balgarskata rap muzika v savremennata balgarska literatura – tekstove, artisti, poslania)“. Literaturata, God. XV, 26. Literaturnata istoria dnes. Chast vtora: 343–362.Bergson, Anri. 1996. Smehat. Ese otnosno znachenieto na komichnoto. Sofia: Sonm.Chang, Jeff. 2005. Can’t Stop, Won’t Stop: A History of the Hip-Hop Generation. New York: St. Martin's Press.Čolović, Ivan. 2008. Balkan – Terror Culture. Beograd: Biblioteka XX vek.Dichev, Ivaylo. 2019. Kulturni stseni na politicheskoto. Sofia: Prosveta.Dimov, Ventsislav. 2012. „„Power to the people” (kam paradoksite na otnosheniyata mediyna muzika – vlast)“. In: Neykova, Maria (sast., red.). Medii, vlast, pari – ima li myasto za kachestvena zhurnalistika. Sbornik „Zhurnalisti po teoria, zhurnalisti na praktika”, Sofia: SU „Sv. Kliment Ohridski”, FZhMK, 77–90.Dimov, Ventsislav. 2013. „Vagner, Volen, Shisharkata, Shamara i ... (Varhu zvukovite obrazi na protesta i tehnite mediyni reprezentatsii)”. In: Angelova, Vyara (sast.) Grazhdani i medii. Sbornik s dokladi ot nauchnata konferentsia „Grazhdani i medii”, 16–17 may 2013 g. Sofia: UI „Sv. Kliment Ohridski”, 307–323.Dimov, Ventsislav. 2014. “Bulgarian Hip-hop Music as a Phenomenon of Alternative Journalism / Болгарская „хип-хоп” музыка как феномен альтернативной журналистики”. В: Сергеева, Т. С. (ред.). Медиаобразы в современном информационном пространстве. Казань: Казанский федеральный университет, 25–52.Dimov, Ventsislav. 2014. „Treska v delnichna vecher (Za mediynata sila na pesenta v edin ne samo akustichen svyat)“. In: Angelova, Vyara, Neykova, Maria, Popova, Zhana (sast., red.) Radio, razkaz, rech. Yubileen sbornik v chest na prof. dsn Snezhana Popova. Sofia: UI „Sv. Kliment Ohridski”, 35–47.Du Gay, Paul, Hall, Stuart; Janes, Linda, Koed Madsen, Anders, Mackay, Hugh and Negus, Keith. 2013. Doing Cultural Studies: The Story of the Sony Walkman. London: SAGE.Fiske, John. 1995. „Popular Culture“. In: Lentrichia, Frank, McLaughlin, Thomas (eds.) Critical Terms for Literary Study. Chicago: The University of Chicago Press, 321–335.Frith, Simon. 1983. Sound Effects: Youth, Leisure and the Politics of Rock ’n’ Roll. London: Constable.Groys, Boris. 2014. Kommunisticheskiy postskriptum. Moskva: Ad Marginem PressGuins, Raiford, Cruz, Omayra Zaragoza (eds.) 2005. Popular Culture. A Reader. London: SAGE Publications.Hall, Stuart. 2005. „Notes on Deconstructing The Popular“. In: Guins, Raiford, Cruz, Omayra Zaragoza (eds.) Popular Culture. London: Sage, 64–71.Laclau, Ernesto. 2005. On Populist Reason. London: Verso.Middleton, Richard. 1990. Studying Popular Music. Philadelphia: Open University Press.Mitchell, Tony (ed.). 2001. Global Noise: Rap and Hip-Hop Outside the USA. Middletown: Wesleyan University Press.Negus, Keith. 1999. Music Genres and Corporate Cultures. London and New York: Routledge.Pasi, Isak. 2001. Smeshnoto. Sofia: IK Trud.Petkov, Vladislav. 2023. „Otvad populizma: kazusat „Pesen za Lena““. Seminar_BG, 26.Peycheva, Lozanka. 2019. „Narodniyat duh“ v avtorskite pesni ot Bulgaria. Sofia: UI „Sv. Kliment Ohridski“.Rayzhekova, Gergana. 2019. Nevidimiyat rok. Alternativnata rok stsena v Bulgaria. Sofia: Intervyu pres.Rikyor, Pol. 1994. Zhivata metafora. Sofia: LIK.Shuker, Roy. 2001. Understanding Popular Music. London and New York: Routledge.Shuker, Roy. 2005. Popular Music. The Key Concepts. London and New York: Routledge.Spasov, Orlin. 2011. „Mediite i politikata: zalezat na chetvartata vlast?“ V: Lozanov, Georgi, Spasov, Orlin (sast.) Mediite i politikata. Sofia: Fondatsia „Mediyna demokratsia“, 221–240.Tagg, Philip.1982. „Analysing Popular Music“. Popular Music, 2: 37–67.Vaysova, Lea. 2023. „Politiki na kontserta: ili kak politicheska partia „Ima takav narod“ specheli sartsata na glasopodavatelite?“. Seminar_BG, 26.Vernallis, Carol. 2013. Unruly Media: YouTube, Music Video, and the New Digital Cinema. Oxford: Oxford University Press.
Keywords: hip-hop culture; alternative media; comic; parody; Jluch; Upsurt; Itzo Hazarta